Low valent lead and tin hydrides in reactions with heteroallenes. Issue 14 (25th March 2021) - Weiß, Sebastian; Widemann, Max; Eichele, Klaus; Schubert, Hartmut; Wesemann, Lars
Abstract : Hydroelementation reactions of low valent tin and lead hydride with heteroallenes are presented. Abstract : Low valent organoelement hydrides of tin and lead, [(Ar*SnH)2 ] and [(Ar*PbH)2 ], were reacted with diorganocarbodiimide and adamantylisocyanate to give products of hydroelementation reactions. Carbon dioxide also reacts with both low valent hydrides, but a reaction product was only characterized in the tin hydride case. A hydride was transferred to the carbon atom and the formed formate anion [HCO2 ] − shows coordination at two tin atoms. Carbon disulfide reacts with the stannyl-stannylene isomer of the low valent organotin hydride. The stannyl part forms a Sn–C bond whereas the stannylene moiety coordinates at the two sulfur atoms. The dimeric organolead hydride exhibits transfer of both hydride ligands to the carbon atom of CS2 to give a dithiol ligand [CH2 S2 ] 2− bridging both organolead units.